Itraconazole resistance in Madurella fahalii linked to a distinct homolog of the gene encoding cytochrome P450 14-α sterol demethylase (CYP51). - Isato Yoshioka; Ahmed Hassan Fahal; Satoshi Kaneko; Wei Cao; Takashi Yaguchi (PLoS Neglected Tropical Diseases)
Background Mycetoma is a deep fungal infection caused by several microorganisms, with Madurella mycetomatis being the most common causative agent. Another related species, Madurella fahalii, is also known to cause eumycetoma. However, unlike M. mycetomatis, M. fahalii exhibits resistance to itraconazole, the standard treatment for eumycetoma, and the underlying cause of this resistance remains unknown. Therefore, understanding the mechanism of this resistance is critical for developing more effective therapies. Principal findings Using the high-quality draft genome sequence of Madurella fahalii IFM 68171, we identified two copies of the gene encoding cytochrome P450 14-α sterol demethylase (CYP51), the target enzyme of itraconazole. These include a gene conserved among Madurella species (Mfcyp51A1) and a M. fahalii-specific gene (Mfcyp51A2). Both genes are actively transcribed in M. fahalii and are upregulated in response to itraconazole. Furthermore, heterologous expression in Saccharomyces cerevisiae revealed that transformants carrying the Mfcyp51A2 gene exhibited reduced susceptibility to itraconazole compared to those with Mfcyp51A1. Conclusion We demonstrated that itraconazole resistance in M. fahalii may be attributed to the presence of an additional CYP51 gene. This study represents the first report on the physiological characteristics of Madurella species using genetic engineering techniques.